1978
DOI: 10.1021/jm00207a030
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-substituted primaquine analogs as potential antimalarials

Abstract: A series of 2-substituted primaquine analogues has been synthesized and evaluated against Plasmodium berghei in the mouse and Leishmania donovani in the hamster. Three members (3a,d,e) of the series were evaluated against Plasmodium cynomolgi in the rhesus monkey. One analogue (3d) was evaluated against Trypanosoma rhodesiense in the mouse, and two (3b,e) were evaluated against Schistosoma mansoni in the mouse. Several analogues possessed significant activity against P. berghei (3e,f) and L. donovani (3a,e).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This produced almost 200 PQ derivatives (Tables 2-4) bearing diverse groups in one or more given positions of the ring [6,46,[161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179]. Globally, the most favourable substituent insertions towards anti-malarial activity where those of methyl groups at positions 4 and 2, tert-butyl at position 2, simultaneous insertion of ethyl substituents at positions 2 and 4 and pentyloxy at position 5, as well as insertion at position 5 of alkoxy, fluoro, and 3-or 4-substituted phenoxy groups [51,163].…”
Section: Modifications At the Quinoline Ringmentioning
confidence: 99%
“…This produced almost 200 PQ derivatives (Tables 2-4) bearing diverse groups in one or more given positions of the ring [6,46,[161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179]. Globally, the most favourable substituent insertions towards anti-malarial activity where those of methyl groups at positions 4 and 2, tert-butyl at position 2, simultaneous insertion of ethyl substituents at positions 2 and 4 and pentyloxy at position 5, as well as insertion at position 5 of alkoxy, fluoro, and 3-or 4-substituted phenoxy groups [51,163].…”
Section: Modifications At the Quinoline Ringmentioning
confidence: 99%
“…Another study on styrylquinolines reported the in vitro activity of the original styrylquinolines on L. panamensis [ 63 ]. In parallel, other series have been prepared with the aim of optimizing 2-substituted quinolines with similar biological properties [ 64 , 65 , 66 , 67 ]. Moreover, quinoline-2-one derivatives exhibited in vitro antileishmanial activity in the range from 1 to 15 µM [ 68 , 69 , 70 , 71 ].…”
Section: The Potential Of 2-substituted Quinolines As Antileishmanial...mentioning
confidence: 99%
“…Since resistance to the 8-aminoquinolines does not appear to be a problem, numerous efforts to create new PrimQ-analogues with improved potential prophylactic action and/or less toxic [167,168]. Now two promising antimalarial agents, 2-tert-butylprimaquine (64) and tafenoquine (65), are available.…”
Section: Design Of Novel Primq Hybridsmentioning
confidence: 99%